Implementasi Dimensi Gotong Royong pada Proyek P5 Siswa Kelas V SDN 7 Kecapi Jepara - Ahadiyah, Nadzifah Mar’atus; Rondli, Wawan Shokib; Riswari, Lovika Ardana (Mataram University, 2025)
The urgency of this study lies in the need for a deeper understanding of the implementation of the Gotong Royong (Collaborative) Dimension within the P5 Project among fifth-grade students at SDN 7 Kecapi. This research aims to analyze the implementation of the Gotong Royong dimension in the P5 Project for fifth-grade students. A qualitative approach with a narrative inquiry method was employed. Data were collected through observations, interviews, and document analysis, and the study was conducted at SDN 7 Kecapi Jepara with fifth-grade students as the research subjects. The findings reveal that the implementation of the Gotong Royong dimension in the Profil Pelajar Pancasila (P5) Project was carried out systematically through an entrepreneurship-themed project titled “Market Day.” The values of gotong royong—including collaboration, empathy, and sharing—were successfully fostered through various activities such as group discussions, task distribution, and hands-on practice in producing and selling products. Through this project, students experienced meaningful learning aligned with the core objectives of the P5 program. They not only acquired knowledge but also developed skills and attitudes reflected in their application of the Gotong Royong dimension during the “Market Day” activities, which were carried out according to procedures and ran smoothly.